Enhancing the Capabilities of Young Russians - Ksenia Kuzmina (Social Work and Society)
Russia is a country with high regional differentiation, where higher incomes are increasingly concentrated in the largest cities, while the transformation of the economic structures in the 1990s in smaller settlements is impeded by the underdevelopment of the necessary infrastructure (Mikhalev, 1998). In fact, the place of residence in Russia defines economic opportunities of people (Ovtscharova, Popova, 2005), as well as educational opportunities, diversity of leisure activities and choice of social services and medical care. So it is obvious that only taking into consideration the regional particularities could make the social policy effective. That is why the doctoral research project takes into account the interregional aspect. For the research it has been chosen North-West region with aged population, low-income employment and with average poverty among families with children (Ovtscharova, Popova, 2005) and Saint-Petersburg as developed industrialized centre.